Geotechnical Challenges and Experiences of Working a Deep and Wide Longwall Face: A Case Study of Adriyala Longwall Project, SCCL - Veera Reddy Boothukuri; Panigrahi Durga Charan; Bhattacharjee Ram Madhav; Gautam Benerjee (International Conference on Ground Control in Mining, 2017)
"India’s tryst with mechanized longwall coal mining started with the introduction of the first self-advancing powered support longwall (PSLW) face at Moonidih Colliery of Jharia Coalfield in 1978 and at Godavarikhani (GDK)7 Incline of Singareni Collieries Company Limited (SCCL) in 1983. During the last 37 years, about 30 longwall units in Coal India, Ltd., (CIL) and 10 longwall units in SCCL have been introduced with powered roof supports of varying capacity, ranging from 280 to 800 tonnes, in many mines in India under varying geological and geotechnical conditions. The majority of the longwall faces in India have been worked under relatively shallow cover (up to 200m), and significant strata control problems have been encountered due to poor caveability of the roof, inadequate capacity of the supports, a lack of knowledge on longwall caving mechanisms, less than adequate strata monitoring systems, and the non-availability of quality spare parts, etc. This has resulted in structural damage to supports and increased downtime of the equipment, thereby making longwall mining in India a case of technology failure. Energy demand for a developing country like India with a population of 1.2 billion is huge, and the thrust on increasing coal production continues. However, the share of coal production from underground mines in India continues to decline (current share is around 6%) because of absence of successful mass production technology in underground coal mining. Under this backdrop, a high-capacity longwall with state-of-the-art technology was introduced in 2014 at Adriyala Longwall Project (ALP) of SCCL for the first time in Indian Coal Mining Industry. The first longwall panel (LWP) has been completed successfully. This paper highlights the major geotechnical challenges encountered during development of the longwall gate roads due to the presence of two overlying clay bands, significant in-situ horizontal stresses and the experience of using rigid (welded) steel wire mesh with resin-anchored roof bolts. Efforts have been made to analyze longwall weighting and caving behavior, such as main and periodic weightings, the effect of front and side abutment pressures, and the behavior of gate roadway support systems under immediate friable weak roof with overlying massive sandstone."